Fluxo de dióxido de carbono e potencial de mineralização de serapilheira em solos sob vegetação clímax de cerrado - Bicalho, Ingrid Mara (2010)
The study was conducted in four distinct classes of soils, namely Yellow Latosol (LAD), Hapludox (RH), Entisol (RQo) and Acrudox typical (LAw), all under savannah vegetation. Four samples were collected per area, in two depths (0-10 and 10-20 cm) and three seasons (summer, winter and spring). An analysis was made on soil chemical and physical and chemical analysis of litter and biochemical. The parameters were: the CO2 flux, microbial respiration, activity of urease and β-glucosidase, the percentage of leaf litter decomposition and total organic carbon (COT). The sites analyzed showed significant differences regarding the chemical properties of soil. The Law soil had the highest CO2 fluxes in times and the minors observed for RQo. No correlation of flow with the concentration of nutrients in the litter. In layer 0 -10 cm, the flow of CO2 was positively correlated with COT, N, K, C / N and C / P. The correlation in the layer 10- 20 cm was positive for the COT and N. The additions of 0.1 and 1% of litter were not sufficient to determine the potential carbon mineralization, only the addition of 10% showed satisfactory results with soil RH presented the largest percentage and was observed for RQo. The major differences in respiration in these soils were observed after the addition of 10% of litter, especially for the RQo. The yield respiratory decreased with increased amount of litter added and the soil had the highest yield for Lad respiratory. The largest differences in yield were observed in the addition of 0.1% of litter. With respect to enzyme activity, the greatest differences were observed in the addition of 10% litter, and soil RQo showed higher activity of the enzyme β-glucosidase and soil RH showed higher activity of the enzyme urease.